Analyzing a project-based blended learning model for citizenship education to foster humanity literacy - Kusnadi, Kusnadi; Sapriya, Sapriya; Budimansyah, Dasim; Wahab, Abdul Azis (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The study aims to develop a Project-Based Learning (PBL) blended learning strategy to enhance the human literacy skills of students taking Citizenship Education in higher education. The research uses the Research & Development (R&D) method combined with the ASSURE model, which involves six stages: analyzing students, expressing goals, selecting methods, media, and materials, using media and materials, requiring student participation, and evaluating and revising. The study uses expert validation, questionnaires, interviews, and a pretest-posttest design to evaluate the effectiveness of the PBL-based blended learning approach. The results indicate that the PBL-based blended learning approach effectively develops humane literacy among Citizenship Education students. The article discusses the importance of human literacy as a 21st-century skill and the development of a blended learning model using the ASSURE model to foster human literacy.